1976
DOI: 10.1002/pssa.2210330106
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature conductivity of undoped and Copper-doped cadmium selenide

Abstract: The electrical conductivity σ of undoped and Cu‐doped CdSe crystals is measured over the range 600 to 1000°C as a function of cadmium and selenium vapour pressure and temperature. The formation enthalpy of the doubly ionized native donor defect (V Se‥ or Cd i‥) is found to be (1.86 ± 0.09) eV at constant cadmium vapour pressure and ⪆ 4.95 eV at constant selenium vapour pressure. For Cu‐doped samples the conductivity varies as pCd1/2 and the electron concentration is almost independent of temperature above 600°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Then E ( + ) and a(-) acquire halfinteger values for copper containing defects. Table 2 shows the expressions of type ( 5 ) for the ENC parts, considering (13) and (14). Values of a(-) are given within the liiriits I n order to finally establish the suitability of (17), it is imperative to take into account that the change of yn = 0.5 -+ yn = 0, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Then E ( + ) and a(-) acquire halfinteger values for copper containing defects. Table 2 shows the expressions of type ( 5 ) for the ENC parts, considering (13) and (14). Values of a(-) are given within the liiriits I n order to finally establish the suitability of (17), it is imperative to take into account that the change of yn = 0.5 -+ yn = 0, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Most numerous are investigations of pure CdSe in cadmium vapour [l to 41 or selenium vapour [3, 51, but in practice more important are doped semiconducting materials, such as copper-doped CdSe. According to Callister et al [S] and Varvas and Nirk [3] copper acts in cadmium vapour at, high temperatures in CdSe as a donor.…”
Section: Introductionmentioning
confidence: 99%
“…Nirk has found that copper is distributed between interstitial sites Cut and associates (CUivCd)' [3]. Recent studies of defect structure [4, 51 indicate that the electron concentration is smaller than the concentration of copper in CdSe, especially in Cd vapour, and therefore the appearance of neutral defects involving copper is possible.…”
Section: Introductionmentioning
confidence: 99%
“…2b can be compared with the value ∆E = 1.5 eV of isobar of undoped CdSe [14]. Earlier [16] we investigated the dependence of HTEC isotherm of ZnSe:In under p Zn as σ ~ Zn p γ , where γ ≈ 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…An exception is CdTe:In with precisely performed high temperature investigations and HTDE models [8][9][10][11]. HTDE of undoped ZnSe [12,13] and CdSe [14] are different. In the present work the results of HTEC measurements are performed in ZnSe:In and in CdSe:In under selenium vapour pressure ( 2 Se p ) and at large crystal temperature range with the aim to find common features and differences in HTDE models.…”
Section: Introductionmentioning
confidence: 96%